2016
DOI: 10.1371/journal.pone.0151753
|View full text |Cite
|
Sign up to set email alerts
|

The Circular RNA Cdr1as Promotes Myocardial Infarction by Mediating the Regulation of miR-7a on Its Target Genes Expression

Abstract: ObjectivesRecent studies have demonstrated the role of Cdr1as (or CiRS-7), one of the well-identified circular RNAs (circRNAs), as a miR-7a/b sponge or inhibitor in brain tissues or islet cells. This study aimed to investigate the presence of Cdr1as/miR-7a pathway in cardiomyocytes, and explore the mechanism underlying the function of miR-7a in protecting against myocardial infarction (MI)-induced apoptosis.MethodsMouse MI injury model was established and evaluated by infarct size determination. Real-time PCR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
268
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 343 publications
(276 citation statements)
references
References 39 publications
7
268
1
Order By: Relevance
“…A previous study has reported that Cdr1as serves as a molecular sponge of miR-7 and conducts important functions in different biological or pathological progresses, including myocardial infarction [32], hepatocellular carcinoma [23], insulin transcription and secretion [22] and brain development [22]. We detected the expression of miR-7 and miR-135a in 29 pairs of bladder cancer tissues and ANTs.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has reported that Cdr1as serves as a molecular sponge of miR-7 and conducts important functions in different biological or pathological progresses, including myocardial infarction [32], hepatocellular carcinoma [23], insulin transcription and secretion [22] and brain development [22]. We detected the expression of miR-7 and miR-135a in 29 pairs of bladder cancer tissues and ANTs.…”
Section: Discussionmentioning
confidence: 99%
“…Though none of these miRNAs are reported in current literature to be directly involved in hypoxia regulation in the liver, they do take part in functional regulation in other organs in hypoxia. For example, miR-7a-5p attenuates post-myocardial infarction remodeling and protects cardiac myocyte from hypoxia-induced apoptosis involving Sp1 and PARP-1 in mice [36-38] and miR-25 protects against hypoxia/reoxygenation-induced fibrosis and apoptosis in cardiomyocytes by targeting HMGB1 [39]. Also, miR-26 is induced in response to low oxygen and decreases proapoptotic signaling in a hypoxic environment [40], while miR-122-5p inhibition attenuates hypoxia/reoxygenation-induced myocardial cell apoptosis by targeting GATA4 [41].…”
Section: Discussionmentioning
confidence: 99%
“…The previously mentioned CDR1as, which mediates the regulation of miR-7 on its target gene expression, has also shown evidence of promoting myocardial infarctions (MIs). A study using MI mice to examine CDR1as and miR-7 demonstrated that CDR1as overexpression in myocardial muscle cells promoted cell apoptosis and that this effect can be reversed by miR-7 overexpression 24 . However, further mechanism to illustrate the CDR1as/miR-7 pathway during MI-induced apoptotic process need to be performed.…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…Genome-wide RNA-sequencing analyses have now identified a considerable number of circRNAs derived from backsplicing. Although they are generally expressed at low levels, increasing evidence has shown that circRNAs are linked to physiological development 15 and different diseases, such as neurological dystrophy, 21 cardiovascular diseases, [22][23][24][25] and cancer. [26][27][28] Recently, circRNAs have also been shown to be enriched and stable in plasma, 29 saliva, 30 and even in serum exosomes, 31 indicating the potential of circRNAs as readable biomarkers.…”
Section: Introductionmentioning
confidence: 99%